Hedgehog pathway proteins and their association with clinicopathological parameters of bladder cancer - Mohd Ariffin, Khairunnisa (2016)
Hedgehog pathway is important for growth and patterning during embryonic development. Previous studies have shown that constitutive activation of Hedgehog pathway can lead to various types of malignancies including medulloblastoma, basal cell carcinoma, gastrointestinal, breast and prostate cancer. The purpose of this study was to investigate the expression of Hedgehog pathway proteins in bladder cancer and determine their association with clinicopathological parameters. The expression of Sonic hedgehog (SHH), its receptor Patched (PTCH1), downstream transcription factor GLI1 and its signal transducer SMO in 112 bladder cancer tissues from Hospital Kuala Lumpur were determined by immunohistochemistry. SHH was expressed in 108 (96.4%) cases, GLI1 in 104 (92.9%) cases, PTCH1 in 111 (99.1%) cases and SMO in all cases. The relationship between the expression of these four proteins and its clinicopathological parameters were analysed statistically. Immunohistochemical staining results showed SHH, GLI1 and SMO proteins were mainly located in the cytoplasm of tumour cells, whereas PTCH1 was mainly located in the nucleus of tumour cells. Positive expression of SHH, PTCH1, GLI1 and SMO proteins were correlated with a few variables which include grade and stage of bladder cancer, lymph node metastasis and distant metastasis (Mx). Among all of the clinicopathological parameters, SMO was found to be the only protein that showed statistically significant association with higher grade (p=0.001) and higher stage (p=0.042) of bladder cancer. SMO expression also showed borderline association with lymph node metastasis (p=0.056). These findings indicate that SMO expression may be a poor prognostic marker in bladder cancer.